Practice of Telehealth in Otolaryngology: A Scoping Review in the Era of COVID-19. (March 2022) - Gonzalez, Joseph N.; Axiotakis, Lucas G.; Yu, Victoria X.; Gudis, David A.; Overdevest, Jonathan B.
Objective: The COVID-19 pandemic has spurred widespread adoption and advancement in telehealth activities, representing a marked change in otolaryngology practice patterns. The present study undertakes a scoping review of research focused on telehealth in otolaryngology (teleotolaryngology) to identify key themes and commonly utilized outcome measures that will assist future development in this growing field. Data Sources: PubMed, Embase, and Cochrane databases and reference review. Review Methods: Per guidelines of the PRISMA Extension for Scoping Reviews, we performed database queries using a comprehensive search strategy developed in collaboration with research librarians at the Columbia University Irving Medical Center. We identified 596 unique references to undergo title and abstract review by 2 independent reviewers, leaving 439 studies for full-text review. Results: We included 285 studies for extraction of notable findings, leaving 262 unique studies after accounting for content overlap. We identified core outcome measures, including patient and provider satisfaction, costs and benefits, quality of care, feasibility, and access to care. Publication volume increased markedly over time, though only 4% of studies incorporated randomized study group assignment. Using an iterative approach to thematic development, we organized article content across 5 main themes: (1) exploration of teleotolaryngology evolution, (2) role in virtual clinical encounters, (3) applications in interdisciplinary care and educational initiatives, (4) emerging and innovative technologies, and (5) barriers to implementation. Conclusion: This scoping review of teleotolaryngology documents its evolution and identifies current use cases, limitations, and emerging applications, providing a foundation from which to build future studies, inform policy decision making, and facilitate implementation where appropriate.